Satirical humor as a tool for political critique: Analyzing the role of MEET NITE LIVE in shaping public perceptions of government policies - Ulfah Rosyidah; Wafirotul Masfuah (Privietlab, 2025)
In the digital era, media plays an essential role in shaping public opinion, with alternative media platforms emerging as key players in critiquing government policies. Among these, satirical content has gained significant traction as a method of social critique. This study investigates MEET NITE LIVE, an Indonesian satirical program, to understand how humor and framing techniques are employed to critique government policies and influence public perceptions. By utilizing a qualitative approach that combines Critical Discourse Analysis (CDA) and Content Analysis, the study explores how the host uses satirical humor—particularly irony, sarcasm, and parody—to frame government policies, highlighting inefficiencies, injustices, and contradictions, particularly within the economic and educational sectors. The research reveals that the humor in MEET NITE LIVE goes beyond mere entertainment. It serves as a tool for social critique, encouraging the audience to critically reflect on pressing socio-political issues. By using humor to expose the flaws in government actions, the show fosters a deeper public awareness, prompting meaningful discussions about the implications of these policies. This study contributes to a deeper understanding of how satirical media, specifically through programs like MEET NITE LIVE, functions as a tool for political discourse. By analyzing the specific humor techniques employed, such as irony, sarcasm, and parody, the research reveals how satirical content critically engages the public with government policies. It demonstrates the potential of satire not only to entertain but also to stimulate critical reflection on socio-political issues, thereby encouraging a more informed and active public engagement with the implications of government actions The findings highlight the importance of alternative media in providing a space for open critique, allowing the public to engage with social and political issues that are often overlooked or constrained by mainstream media. These findings emphasize the role of alternative media in expanding the public discourse, which in turn can have a significant impact on shaping opinions and policies.